Exploring the Relationship between Transformational Leadership and Innovative Work Behavior: A Systematic Literature Review - Sueb Sueb; Sopiah Sopiah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Transformational leadership encourages employees to take initiative, think creatively, and take risks in achieving organizational goals. The aim of this study is to provide an overview of transformational leadership and innovative behavior, explore the factors that mediate the relationship between transformational leadership and innovative behavior, and evaluate the influence of transformational leadership and innovative behavior by conducting a review of journals published in Scopus through